Perkembangan Teknologi di Bidang Produksi Pangan dan Obat-obatan serta Hak-hak Konsumen - Nurhayati Abbas (Fakultas Hukum Universitas Islam Indonesia, 2009)
Nowadays, the regulation on food and drugs is considered to be clear and sufficient. However, the duty to examine, supervise and to avoid the dangers which are possible to happen, is not yet been undertaken. In addition to this, thre is no relevant body establisehed for such puposes. Therefore, the wise step to avoid any negative impacts of food and drugs is by incepting a regulation to supervise importing, consuming and the sirculation of such products.Keywords: food production, drugs, consumers’ rights